PERIODONTAL STATUS OF FIRST MOLARS DURING ORTHODONTIC TREATMENT - Ahmed, Imtiaz; Haque, Saif ul; Nazir, Rozina (Journal of Ayub Medical College Abbottabad, 2011)
Background: The most important aetiological factor of periodontal disease is plaque deposition around gingival margin. The aim of the study was to investigate the negative changes in periodontal health (increase in pocket depth) of first molars in fixed orthodontic treatment and to discuss the available options to avoid it. Methods: Group A (6 month of treatment) comprised of 45 patients, compared to Group B (12 month of treatment) comprised of 45 patients. Initial pocket depth of first molars checked before placement of molar bands in both groups of patients, then for Group A patients pocket depth evaluated after 6 month of treatment and for Group B patients pocket depth evaluated after 12 month of treatment period. Results: In patients with 6 months of treatment the pocket depth of molars mostly falls between 1.5 and 2.0 mm. In some severe cases it exceeded 3 mm. In patients at 12 months of treatment pocket depth was greater than 6 month group and it mostly fell in the range of 2.0-2.5 mm. Conclusion: Increase in pocket depth showed that plaque deposition leads to periodontal destruction around molar bands. Patient motivation to maintain oral hygiene and regular scaling will minimise hazardous effects. Keywords: Pocket depth, Gingivitis, Oral hygiene, fixed orthodontics